PASANG SURUT GERAKAN BURUH INDONESIA - Bambang Sulistyo (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2018)
This paper studies labor movement in Indonesia and it attempts to understand the reason of the distancing of relation between labor and the society. Labor activities in demonstration actions were not seen by the society as a struggle for equal conditions but are seen as threats to public order within the society.By tracing labor history in Indonesia since the forced cultivation era in th e19th centurywhich can be seen as the moment of the emergence of labor in Indonesia, it can be seen that at the time there were close connections between labor and societies who both worked to liberate the Indonesian society from colonial domination and to create a state who would improve the welfare of the society and labor themselves. This paralel view would later chanfe after the 30 September tragedy when labor were coopted by the New Order regime and through indoctrination were seperated from the society.This paper will also explain that labor movement in Indonesia does not follow the conceptof class consciousnees as in the West, but based on ethnic and cultural identities and on types of occupation.